Vertical Phosphorus Migration in a Biosolids-Amended Sandy Loam Soil in Laboratory Settings: Concentrations in Soils and Leachates - Yulia Markunas; Vadim Bostan; Andrew Laursen; Michael Payne; Lynda McCarthy (Applied and Environmental Soil Science)
The impacts of biosolids land application on soil phosphorus and subsequent vertical migration to tile drainage were assessed in a laboratory setup. Soil, representing typical “nonresponse” Ontario soil as specified by Ontario Ministry of Agriculture, Food, and Rural Affairs (OMAFRA), was amended with anaerobically digested biosolids at a rate of 8 Mg ha−1 (dry weight). Over five months, these amended soil samples from two different depths were sequentially fractionated to determine various inorganic and organic phosphorus pools in order to evaluate phosphorus vertical migration within a soil profile. Soil leachate was analyzed for soluble reactive phosphorus. The results indicated that biosolids application did not significantly affect phosphorus concentrations in soil and did not cause phosphorus vertical migration. The concentrations of soluble reactive phosphorus also were not significantly affected by biosolids.